Influence of an object's z-axis location and location on the axial plane on the voxel value representation and uniformity in cone beam computed tomography - Kanako Nishino (2018)
© 2014 Elsevier Inc. Objective This study aimed to determine the influence of an object's z-axis location and location on the axial plane on the voxel values in cone beam computed tomography.Study Design The CTP401 and CTP486 of the Catphan 500 phantom were scanned with an Alphard-3030 at 6 locations in the z-axis.Results In CTP401, the voxel values of 3 inserts showed the lowest values when the center of the radiation field corresponded to under 2 or 4 cm of the z-axis center of CTP401. In CTP486, the voxel values showed the lowest values when the center of the radiation field corresponded to under 2 or 4 cm of the z-axis center of CTP486. On the same axial plane, the voxel values at the center showed significantly lower values than the off-center locations (P =.002).Conclusions The voxel values in the Alphard-3030 changed based on the z-axis location of the radiation field and were nonuniform on the same axial plane.